2014
DOI: 10.1111/cjag.12043
|View full text |Cite
|
Sign up to set email alerts
|

Farm Support Payments and Risk Balancing: Implications for Financial Riskiness of Canadian Farms

Abstract: Risk balancing refers to the balancing of business risk (BR) and financial risk (FR) by firms through their investment and borrowing decisions. Assuming the concept holds, a decrease in income variability (BR) prompts the firm to incur greater debt levels thereby increasing FR. Reducing (BR), which continues to be the central objective of Canadian agricultural policy through programs such as Canadian Agricultural Income Stabilization Program (CAIS)/AgriStability, may lead farmers to take on more FR than they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 16 publications
2
25
1
Order By: Relevance
“…For example, from the results in Table it can be seen that participating in these programs does not result in reduced variability in performance as measured by the standard deviation. This result is consistent with Uzea et al () who found that BRM program participation did not reduce business risk for field crop operations in Ontario. Instead, risk reduction benefits are due in large part to the fact that the increase in expected performance outweighs the slight increase in variability, so that in relative terms (i.e., the CV) risk is reduced.…”
Section: Discussion and Policy Implicationssupporting
confidence: 92%
“…For example, from the results in Table it can be seen that participating in these programs does not result in reduced variability in performance as measured by the standard deviation. This result is consistent with Uzea et al () who found that BRM program participation did not reduce business risk for field crop operations in Ontario. Instead, risk reduction benefits are due in large part to the fact that the increase in expected performance outweighs the slight increase in variability, so that in relative terms (i.e., the CV) risk is reduced.…”
Section: Discussion and Policy Implicationssupporting
confidence: 92%
“…During the last decades a wealth of literature has emerged about the impacts of agricultural policy on farm income risks (el Benni and Finger, 2013;de Mey et al, 2014;Uzea et al, 2014;Severini and Tantari, 2015;de Mey et al, 2016, Severini et al, 2016. Previous research findings suggest that agricultural policy measures may affect farmers' income risks via diverse pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of subsidized insurance may also encourage D r a f t farmers to take more risk in other aspects of their business operations, such as investments in additional land, new equipment, or other improvements that involve taking on more risk (Rude 2008). Gabriel and Baker (1980) and Uzea et al (2014) showed that farmers make financial adjustments leading to increased financial risks in response to lower business risks that result from stabilization. Lower risks and increased expected returns also lead to increased leverage resulting in more debt.…”
Section: Risk and On-farm Decisionsmentioning
confidence: 99%